Aspirin and recurrent venous thromboembolism. (March 2013) - Prandoni, P; Noventa, F; Milan, M
While there is conclusive evidence that aspirin plays a role in reducing the risk of clinically relevant venous thromboembolism (VTE) arising in a number of surgical and non-surgical situations at risk, little is known of the potential of aspirin for the long/term prevention of recurrent VTE. In two recent multicentre, double-blind studies (WARFASA and ASPIRE), the efficacy and safety of a low dose of aspirin (100 mg per day) were assessed in patients with unprovoked VTE who had completed an initial period of conventional treatment with vitamin K antagonists. The two studies used identical aspirin regimens and had similar enrolment criteria and outcome measures. When data from these two trials were pooled, there was a 32% reduction in the rate of recurrence of VTE (hazard ratio [HR], 0.68; 95% confidence interval [CI], 0.51–0.90) and a 34% reduction in the rate of major vascular events (HR, 0.66; 95% CI, 0.51–0.86). Moreover, these benefits were achieved with a low risk of bleeding. As patients with previous symptomatic atherosclerosis were not enrolled in these two studies, whether these results apply also to this category of patients is uncertain. We recently had the opportunity to review the clinical charts of 1919 consecutive patients presented with a first episode of VTE, which was either unprovoked or triggered by transient risk factors, and were followed up for an average period of four years after discontinuing anticoagulation. The rate of recurrent VTE in the 256 patients with a history of symptomatic atherosclerosis who had been given 80–160 mg of aspirin once daily (17.2%) did not differ from that (19.9%) observed in those without atherosclerosis who were left without any antithrombotic treatments. The implication of this observation is that whenever patients with symptomatic atherosclerosis are deemed to require long-term protection against recurrent VTE, they are unlikely to benefit from (resuming) aspirin. Conversely, aspirin in low doses offers an appealing, safe and highly cost-effective option for the long-term prevention of recurrent events in patients with unprovoked VTE who are free from symptomatic atherosclerotic lesions.